Bambara Groundnut Rhizobacteria Antimicrobial and Biofertilization Potential - F. Ajilogba, Caroline; Babalola, Olubukola O.; Adebola, Patrick; Adeleke, Rasheed (Frontiers in Plant Science, 2022)
Bambara groundnut, an underutilized crop has been proved to be an indigenous crop in Africa with the potential for food security. The rhizosphere of Bambara groundnut contains Rhizobacteria with the ability to grow, adapt and colonize their surroundings even in unfavourable conditions and have not been explored for their plant growth-promoting properties. The aim of this research was to determine the potentials of rhizobacteria from Bambara groundnut soil samples as either biofertilizer or biocontrol agents or both to help provide sustainable agriculture in Africa and globally. Analyses of Bambara groundnut rhizospheric soil samples included chemical analysis, Plant growth-promoting activities, antifungal assay Phylogenetic analysis using 16S rRNA was also carried out on the isolates to identify the rhizobacteria. A 2-year field study planting was carried out to determine the effect of these rhizobacteria as biofertilizers for bambara groundnut (Vigna subterranea). The study was carried out in complete randomized block experimental design with three replications. All the isolates were able to produce ammonia and 1-aminocyclopropane-1-carboxylate while 4.65%, 12.28% and 27.91% produced Hydrogen cyanide, Indole acetic acid and solubilized phosphate respectively, making them important targets as biocontrol and biofertilizer agents.. The field results revealed that treatment with rhizobacteria had significant results compared with the control. Characterization of selected isolates reveals their identity as B. amyloliquefaciens, B. thuringiensis and Bacillus sp. These Bacillus isolates have proved to be plant growth-promoting agents that can be used as biofertilizers to enhance the growth of crops and consequent improved yield. This is the first time the rhizobacteria from the bambara groundnut rhizosphere is applied as biofertilizer.